EFEKTIVITAS KOORDINASI PELAYANAN KESEHATAN PENGUNGSI DI POS PENGUNGSIAN MAGUWOHARJO PADA MASA TANGGAP DARURAT BENCANA GUNUNG MERAPI PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2010 - , Enik Listyaningsih; , dr. Yodi Mahendradhata., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The eruption of Mount Merapi in Yogyakarta has caused dangerous impact to the peopleâs health. It is important to provide a good health care services during emergency response. Maguwoharjo is a shelter with the largest number of refugees. However, there is a problem because the health care staffs are not well distributed in that shelter. The coordination on health care service is important to overcome the health problems during emergency response. Methods: This is a qualitative study using in-depth interviews method to collect data. The informants are representatives from Yogyakarta provincial health office, Sleman district health office, primary health care center of Depok, Non Government Office/NGO, and former refugees. To ensure the validity of data, we do the triangulation. Results: The coordination of health care service to refugees is studied from its communication and organization. The communication was done by regular meetings in the morning and in the afternoon involving shelterâs coordinator, volunteerâs coordinator, and representative from both provincial and district health office. Not only by the regular meeting, but also by using SMS gateway and skype (internet-based). There was also a hierarchial structure to organize all health care staffs and their responsibilities during emergency response. Until the end of the evacuation, there was no outbreaks, incidence of disease was dcreased, and infectious disease controlled. However, it still not enough of health care personels, lack of adequate facilities, and unavailable of operating standard procedure regarding to provide good health services to refugees. Conclusion: The coordination of health services to refugees during the emergency:It is effective but still need to improve the information to the refugees and the volunteers,and the provincial health department and the country health department should have SOPs.